Analysis of induced Traffic Alert and Collision Avoidance System collisions in unsegregated airspace using a Colored Petri Net model. (March 2015) - Jun, Tang; Piera, Miquel Angel; Nosedal, Jenaro
For rigorously safe aviation, it is of great significance to conduct an analysis of the current and new operations, providing a global perspective of the scenario dynamics and a better understanding of the potential collision occurrence for risk assessment. The objective of this study is to consider a number of the difficulties that are involved when establishing a validation of the Traffic Alert and Collision Avoidance System (TCAS), which constitutes the last resort for reducing the risk of near mid-air collisions between aircraft in a multithread scenario, and to analyze the TCAS logic using a causal model. In this paper, the causal model that is specified in the Colored Petri Net (CPN) formalism is employed as a key approach to analyze quantitatively the state space of a congested traffic scenario in which the events could transform a conflict into a potential collision. It offers a rigorous tool not only for TCAS validation but also for the analysis of a wide range of properties of the TCAS behavior. This CPN model assumes unrestrained initial positions and TCAS II-equipped aircraft; it is demonstrated to be extremely effective for generating all possible future TCAS failure end-states from the current locations, and the Interactive Collision Avoidance Simulator EuroControl simulator is used to illustrate the collision process of a three-aircraft scenario.